Effects of temperature and velocity on chlorine dispersion in an indoor storage system using computational fluid dynamics simulation - Safakar, Mohsen (2014)
The manufacturing companies producing chemical products have to deal with a variety of inherent environmental risks in conducting their operations. Nowadays, the indoor release of hazardous chemical gases which are heavier than the air is one of the risks that require an in-depth scrutiny. The reason for this claim is that the dense clouds of gases have a tendency to initially flow on the ground level, which in turn, causes fatal injuries or other potential health threats to human beings. Although the existences of these gases are dangerous, factories are not able to reduce their emissions risk to an absolute zero amount. Consequently, it is important to investigate what factors affect the indoor movements and dispersions of the heavierthan-air dangerous gases. In this study, computational fluid dynamics (CFD) software using FLUENT 14.5 code was employed in order to model the accidental indoor dispersion of a common dense gas, chlorine, from a small undetected leak into an indoor industrial environment. Computational fluid dynamics (CFD) has outstanding capabilities in illustrating realistic simulations even for the cases of geometrically complex scenarios. Results of the simulations showed that the chlorine dispersion would behave like the liquid when it was being flown on any surface. Moreover, it was found that the chlorine density gradually increased on the ground level. Specifically, findings from this research revealed that mixing results for chlorine dispersion patterns are subject to different levels of temperature, wind amount, and wind direction. There is a direct relationship between temperature and chlorine gas dispersion. To support, among the temperatures studies in this research, namely 270K, 297K, and 315K chlorine gas dispersion was the highest at temperature 315K, ranging from 8×10-3 to 1×10-2 ppm. This study also showed the effect of wind velocity on chlorine gas dispersion at different temperatures. Specifically, at 270K, chlorine gas dispersion was 0.001 - 0.595 ppm, 0 - 0.0005 ppm, and 0 - 0.005 ppm at the wind velocities 1 m/s, 3 m/s, and 5 m/s, respectively. However, chlorine gas dispersion with the same wind velocity speeds remained constant, within the range of 0 - 0.005 ppm. All of these factors had significant relations with chlorine dispersion in indoor environment. In this research, the effects of ventilation on dispersion of chlorine were analyzed and their results were compared with wind velocity simulations Overall, the effects of the environmental factors with the release and spread of chlorine in indoor space were meticulously investigated.